New type of hybrid nodal line semimetal in Be2Si. (28th March 2019) - Li, Z H; Wang, W; Zhou, P; Ma, Z S; Sun, L Z
Abstract: Following Dirac and Weyl semimetals, nodal line semimetals represent a new type of topological semimetal and attracted extensive interest in modern condensed matter physics. Recently, a kind of hybrid nodal lines have been proposed (Zhang et al 2018 Phys. Rev. B97 125143) and it mainly come from anisotropy interaction. Based on the first-principle calculations and k·p model, we predict a cubic Be2 Si with topological nontrivial electronic states exhibiting fascinating type-I and type-II hybrid nodal line around Fermi level. Unexpectedly the low energy electronic states of Be2 Si are isotropy in kx and ky directions and a new effective model has been proposed for the appearance of this new type hybrid nodal line. The four-fold degenerated type-I and type-II nodal points in the hybrid nodal lines along the high symmetry lines of Γ– K and Γ– X are protected by mirror reflection, time reversal and space inversion symmetry. The spin–orbit coupling effect only induces slight band gap in the hybrid nodal lines in Be2 Si whose nontrivial nature remains. Moreover, the nontrivial hybrid nodal lines in Be2 Si are robust to external strain. The results in present work indicate that Be2 Si are promising candidates for future experimental studies of nontrivial topological semimetals and an excellent platform to study the interaction between the two types Dirac fermions.